An Experimental Study on Dependence of Time Intervals for Connections on Optimization Computations for Task of Aircraft Scheduling - Graf, Vojtech; Teichmann, Dusan; Dorda, Michal (Communications - Scientific Letters of the University of Zilina, 2015)
Mathematical models are often employed for optimization of different problems arising in transport. It is a well-known fact that calculation times, which are necessary to find out an optimal solution, usually increase together with increasing scale of mathematical models (scale is defined by the number of variables and constraints that form each mathematical model). For some types of linear models (usually for the models in which logical or integer variables are used) it often happens that if scale of the model exceeds a certain limit, the model can be solved exactly either with big difficulties or cannot be solved at all. It is also known that the limit for which the model has the problem with its solvability depends on the type of the model. The paper is focused on an estimation of the solvability limit for the task of optimal aircraft scheduling for a charter airline.
Keywords: aircraft scheduling; Linear programming; scale; solvability